Film thickness effect on formation of ultrastable metallic glasses. (May 2021) - Sun, Qijing; Miskovic, David M.; Ferry, Michael
Abstract: Ultrastable metallic glasses (SMGs) formed by physical vapor deposition are an interesting new class of material, exhibiting enhanced stability argued to be equivalent to conventionally quenched metallic glasses that have been aged for thousands of years. The factors controlling the formation and structural development of SMGs are still not well understood. For the first time, the impact of film thickness toward the development of SMGs was explored. By controlling the thickness, we can tune the thermophysical and mechanical properties of SMGs. Geometrical and statistical analyses indicate that the films initially contain loose-packing phases that tend to elongate and present with a larger average size and less dispersive distribution as a result of induced geometric confinement. As the film is built up, structural heterogeneity develops, leading to variations in properties as the glass undergoes rejuvenation. This study provides direct evidence for the structural changes underlying the unique properties of SMGs and challenges the empirical rules for SMGs design. Graphical abstract: Image 1 Highlights: Structure of thinner SMGs exhibit directional strain due to geometric confinement. SMGs undergo rejuvenation as film thickness increases. A shift in the formation mechanism from island to more homogeneous growth occurs as film is built up. The likelihood of SMG formation was reduced as film thickness increases. The impact of enhanced surface mobility upon the kinetics of SMGs extends further than a few nanometers.